Two-stage palm kernel shell washing with water and acetic acid as preparation of co-firing system with coal (Rudarsko-geološko-naftni zbornik, 2024)
Palm kernel shells (PKS) were washed with water and glacial acetic acid (CH3COOH) gradually to prepare them for co-firing with coal. They were then torrefied at 450ºC for one hour. Washing was done to reduce the concentration of ash and alkaline oxides, which would reduce the chance of slagging and fouling. The research was conducted considering that information about washing the PKS with acetic acid and then having them torrefied is very limited and unclear. The results showed that washed and torrefied PKS had better characteristics than those of raw PKS or PKS washed with water. PKS that is washed with acid, torrefied and then blended with coal has low slagging and medium fouling tendencies. However, based on ash fusion temperature, the inclination towards slagging and fouling is high under reducing conditions and medium under oxidation conditions.